2010
DOI: 10.3130/jaabe.9.55
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Role of Gardening and Planning of Green Environments for Daily Use by Residents in Senior Housing

Abstract: This study examines and analyzes the current state of gardening facilities for residents in 11 senior citizen housing complexes and their understandings, actual gardening behaviors and their effects. The objective is to suggest a direction for the planning of gardening and its spatial composition in senior housing complexes. The study used surveys and interviews and conducted field visits to examine actual gardening facilities. The study produced the following outcomes. 1) Elderly people had high expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…With its abundance of microbial and faunal life and its ability to spring forth flowers and food, there is no wonder that soil is a joy for so many, in which to work, play, and dream. Indeed, the practice of gardening is recognized as a viable treatment for patients with a wide range of mental and emotional conditions, including transitioning from correctional institutes to freedom (Rice and Remy, 1998) and providing recreation for seniors (Kim and Ohara, 2010). In addition, evidence exists for more rapid recovery from physical trauma and surgery just by viewing gardens, while healing gardens have become an important component of hospital design (Cooper and Barnes, 1999).…”
Section: Cultural and Spiritual Servicesmentioning
confidence: 99%
“…With its abundance of microbial and faunal life and its ability to spring forth flowers and food, there is no wonder that soil is a joy for so many, in which to work, play, and dream. Indeed, the practice of gardening is recognized as a viable treatment for patients with a wide range of mental and emotional conditions, including transitioning from correctional institutes to freedom (Rice and Remy, 1998) and providing recreation for seniors (Kim and Ohara, 2010). In addition, evidence exists for more rapid recovery from physical trauma and surgery just by viewing gardens, while healing gardens have become an important component of hospital design (Cooper and Barnes, 1999).…”
Section: Cultural and Spiritual Servicesmentioning
confidence: 99%
“…Furthermore, the ratio proposed by Eurostat [98] was not considered consistent with the common size of housing in which Italian older people live. With regard to room type, the presence of more than one bathroom [79], a caregiver's room [46,85], and outdoor spaces [26,41,48,85,99] are cited as age-friendly features and were then included in the metric. Regarding the layout of the dwellings, authors reported the positive effects of having semi-open plan [48] and of reducing the number of doors, hallways, and rooms [69], above all for people living with dementia [85,94].…”
Section: Discussionmentioning
confidence: 99%
“…This form of measurement has been introduced in the metric. Findings report that outdoor spaces offering an accessible extension to the home, like balconies, gardens, patios, and terraces, are positively associated with the wellbeing of older people [26,41,48,85,99]. The positive effects of exposure to daylight, the contact with nature and the physical activity of gardening are some of the reasons why older people experience physical and mental benefits.…”
Section: Types Of Roomsmentioning
confidence: 99%
“…This may relate to a lack of communal space for residents to interact 25. Several small studies also suggested that the design of communal spaces, and activities they supported (eg, gardening), were important for mental health 33 34. However, as with most apartment-level and building-level studies, these studies lack the specificity needed to inform evidence-based policy.…”
Section: Introductionmentioning
confidence: 99%